Elaboración de un plan de mejora de la cultura organizacional para la empresa Importaciones Marcos, Ibarra provincia de Imbabura - Huera Lara, Alicia Estefanía (2023)
This research has been conducted at 'Marcos Imports' to assess the company's organizational culture, identify its weaknesses, and develop appropriate strategies to reinforce it. Establishing a strong organizational culture is crucial for long-term sustainability and empowers all employees within the company. The study used a quantitative methodology with a descriptive scope, examining attributes, characteristics, and factors related to the phenomenon under investigation. It followed a non-experimental design, where variables were not manipulated\; instead, data was collected at a single point in time using a Likert-type questionnaire based on the W. E. N. S. The questionnaire was administered to 12 employees of the organization\; the findings indicated that variables like morale and satisfaction, communication, and conflict resolution had a moderate incidence, while attitude towards change and decision-making showed predominantly negative results, this indicates the need for the implementation of improvements, as not all employees feel well-adapted in their roles, some employees fear communicating with their immediate supervisors, and the opinions of the team members are often overlooked. Moreover, there is no established procedure for resolving conflicts, and quick decisions are made to avoid upsetting anyone\; however, these issues can be addressed through concrete strategies proposed in this study, taking the organizational structure of the company into account.